Understanding the Extracellular Matrix to Enhance Stem Cell-Based Tissue Regeneration - Niklason, Laura E. (Cell Stem Cell, 2018)
The extracellular matrix is a biologically critical entity that has historically been poorly understood. Here we discuss how new tools for characterizing matrix composition and function enable us to design and deliver advanced matrices in vitro, to optimize regeneration, and in vivo, within a variety of tissues and organs.